A career counseling framework for the urban poor - Carlos, Judy Lee; Gomez, Marie Grace A.; Bawagan, Aleli B.; Muega, Maricris B. Acido; Javiniar, Joel C.; Salubayba, Teodora M. (Quezon City College of Education, University of the Philippines Diliman, 2019)
To extend guidance and counseling to the urban poor, an organized system of thought is necessary. However, a career counseling framework for the urban poor has to be established. This study sought to create such a framework for Makati indigent residents. Result to four questions were determined. First, poverty is perceived by the urban poor as scarce food intake due to unstable source of income. Second, the poor attempt to alleviate from poverty by budgeting of resources and borrowing money. Third, career counseling is when, after seeking help, the problem and personal characteristics are evaluated. Fourth, the framework calls for the counseling provider to be trustworthy, pragmatically maximizing available resources so the urban poor will have a more stable source of income to have access to food. Through Charmaz's Constructivist Grounded Theory, strengthening of ties between the indigent community members and the social workers assigned to the area is recommended.
Dissertation (Doctor of Philosophy in Education - Guidance)--University of the Philippines, Diliman
Includes bibliographical references (pages 168-104).
Keywords: Vocational guidance -- Philippines -- Makati City; Counseling -- Philippines -- Makati City; Urban poor -- Philippines -- Makati City; Counseling -- Vocational guidance